The impact of fiscal transfers induced by emissions taxes in stock-flow pollution problems with regions and population mobility - Chan, Felix; Petchey, Jeffrey (Curtin University, 2016)
There is a long-standing literature on the potential for the fiscal transfers induced by taxes on emissions to produce a double dividend. This has taken place within the context of static models without regions or population mobility. In this paper, we examine the potential effects of fiscal transfers induced by emissions taxes in a stockflow pollutant problem over multiple regions in the presence of population mobility. We show that the induced fiscal transfers influence the time chosen by a social welfare maximising decision maker to converge to sustainable pollutant stock targets. The precise impact of the induced fiscal transfers on the convergence time is shown to depend upon the nature of the stock-flow problem and in particular whether the current pollutant stock exceeds or is less than the sustainable level